Citizen‐science data provides new insight into annual and seasonal variation in migration patterns. Issue 1 (28th January 2015) - Supp, S. R.; La Sorte, Frank A.; Cormier, Tina A.; Lim, Marisa C.W.; Powers, Donald R.; Wethington, Susan M.; Goetz, Scott; Graham, Catherine H.
Abstract : Current rates of global environmental and climate change pose potential challenges for migratory species that must cope with or adapt to new conditions and different rates of change across broad spatial scales throughout their annual life cycle. North American migratory hummingbirds may be especially sensitive to changes in environment and climate due to their extremely small body size, high metabolic rates, and dependence on nectar as a main resource. We used occurrence information from the eBird citizen‐science database to track migratory movements of five North American hummingbird species ( Archilochus alexandri, A. colubris, Selasphorus calliope, S. platycercus, and S. rufus ) across 6 years (2008–2013) at a daily temporal resolution to describe annual and seasonal variation in migration patterns. Our findings suggest that the timing of the onset of spring migration generally varies less than the arrival on the wintering grounds. Species follow similar routes across years, but exhibit more variation in daily longitude than latitude. Long distance migrants generally had less annual variation in geographic location and timing than shorter distance migrants. Our study is among the first to examine variation in migration routes and timing for hummingbirds, but more work is needed to understand the capacity of these species to respond to different rates of environmental change along their migratory routes.